METHODOLOGICAL BASIS FOR THE APPLICATION OF COSMISM TO THE DEVELOPMENT OF PEDAGOGICAL THEORY AND PRACTICE - Riza A. Khalilov (Lomonosov Moscow State University, 2022)
Th e relevance of the stated issue is connected with the incompleteness of the transformation in modern education, which requires the search for innovative tools and methods to solve existing problems. Th e application of cosmism methodology to pedagogical practice seems important in the context of educational system modernization based on the principles of personality-oriented education and universal values. Taking into account the insuffi cient knowledge of the ontology of pedagogical cosmism, the chosen direction of research seems to be relevant. Th e purpose of the work is to study practice-oriented application of the ideas of cosmism in the framework of humanistic paradigm development to student-centered education in modern educational environment. Results. Th e most signifi cant results of the study, characterizing its scientifi c novelty, are the following: Халилов Р.А. Методологическая основа применения космизма для развития педагогической теории... Вестник Московского университета. Серия 14. Психология. 2022. № 1 249 1. Th e methodological basis of the concept of cosmism lies in the assumption of the organic unity of Man, Mankind and the Cosmos, supporting the legitimacy of cosmic consciousness as a concept, defi ning Man as a unique Microcosm. 2. In the framework of the pedagogical concept of cosmism, the main direction is the spiritual education of the child, which consists in the discovery of the "higher self ", controlling all spheres of the personality. It also involves the improvement of the emotional, mental, physical and spiritual spheres of personality in order to form a unique quality, elevating a person to the next stage of spiritual evolution. 3. Modern trends in educational policy are consonant with the ideas, formed in pedagogical concept of cosmism. Th ey include systemic integrity of the tasks, principles and directions of education and upbringing, regarding education as a process of development, and the ability of self-improvement of the individual. 4. Application of the ideas of cosmism is focused on solving the problems that modern education faces, including the ethical problem of education and the search for the best solutions to develop talents. Th ese problems also include pedagogical assistance to self-improvement, and foundation of a new type of school, supporting sustainable and continuous development. Conclusion. On the basis of the concept of cosmism and of the methodological guidelines of cosmopedagogy, analyzed in the work, it was concluded that comprehensive development of the individual is possible through the disclosure of creative energy aimed at harmonizing the inner world.